A New Integration System for Natural Gas Combined Cycle Power Plants with CO2 Capture and Heat Supply - Yue Hu; Yachi Gao; Hui Lv; Gang Xu; Shijie Dong (Energies, 2018)
Although carbon mitigation in power industry is attracting more and more attention around the world, the large scale application of carbon capture technology is obstructed because of the enormous energy consumption and huge capital investment required. In this study, an integrated system with power generation, CO2 capture and heat supply are proposed, which adopts three measures to reutilize the waste heat released from the CO2 capture process, including extracted steam recirculation, a CO2 Rankine cycle and a radiant floor heat subsystem. Amongst these measures, the radiant floor heat subsystem can efficiently reuse the relatively low temperature waste energy in the absorbent cooler. Through thermodynamic analysis, it is determined that the power output of the new integrated system is 19.48 MW higher compared with the decarbonization Natural Gas Combined Cycle (NGCC) power plant without system integration. On the other hand, 247.59 MW of heat can be recovered through the radiant floor heat subsystem, leading to an improved overall energy efficiency of 73.6%. In terms of the economic performance, the integration requires only 2.6% more capital investment than a decarbonization NGCC power plant without system integration and obtains extra revenue of 3.40 $/MWh from the simultaneous heat supply, which reduces the cost of CO2 avoided by 22.3%. The results prove the economic and efficiency potential of a NGCC power plant integrated with carbon capture, which may promote the industrial demonstration of carbon capture theology.